Mekanisme Pendaftaran Hak Tanggungan Elektronik Dan Akibat Hukumnya - Meyer Simatupang, Frans (Recital Review, 2022)
Basically granting Mortgage Rights must be done by the owner himself, but if a legal action cannot be carried out by the person concerned himself in a situation then he can authorize his actions to someone appointed so that if the giver of Mortgage can not face himself to the PPAT, then he can appoint someone to act on his behalf by first making a Power of Attorney Imposing Mortgage Rights. At present SKMHT cannot be facilitated by the electronic Mortgage Registration System. The electronic registration system itself goes through two registration processes, namely the fulfillment of debtor and creditor data by the Bank as creditor and data delivery by PPAT as a notary public as a partner of the Bank as creditor. If there is an error in the compilation by the creditor regarding the data of the debtor’s data, this can be a risk if there is a request for confiscation and the APHT will be canceled by law. The Electronic Registration process is also an obstacle if the PPAT is late in submitting it to the Land Agency because it has been recorded when the registration was carried out by the Bank as the creditor. Regarding the delay in submitting APHT, this could also be a risk in the Court of the object of the Underwriting Right and would place the Underwriting Creditors do not yet have a preference for paying off their receivables or are still concurrent credit. ABSTRAK Akta hak tanggungan dan peranan PPAT pengajuan pembebanan jaminan melalui hak tanggungan biasa hingga hak tanggungan dengan elektronik dalam perspektif hukum di Indonesia.Tipe penelitian ini ialah hukum yuridis normatif, dengan pendekatan perundangundangan (statute approach) dan pendekatan konseptual (conceptual approach), melalui bahan hukum primer, sekunder dan tertier. HT-el mulai berlaku pada tanggal diundangkan, PPAT dan BPN perlu kesiapan dalam pelaksanaan meliputi beberapa faktor, baik faktor internal maupun faktor eksternal, pemerintah juga wajib berbenah dengan melakukan tindakan yang bersifat tidak hanya preventif namun juga represif. Dalam prakteknya, tidak adanya pembatasan subjek yang dapat menjadi pemberi HT tersebut menimbulkan permasalahan.Isu hukum yang diteliti dalam tulisan ini adalah kelemahan dan kelebihan serta aturan-aturan yang dapat mengakomodirnya.Menjadi permasalahannya.Bagaimana kedudukan PPAT dalam layanan HT dan HT-el?dan jaminan hak tanggungan dan jaminan hak tanggungan elektronik terhadap pihak ketiga? Sehingga perlu adanya koordinasi terkait antara para pihak yang berkepentingan untuk membahas lebih lanjut mengenai persoalan HT-el perlu disikapi dengan bijak. Â Â